Experimental and theoretical investigation of corrosion inhibition effect of two 8-hydroxyquinoline carbonitrile derivatives on mild steel in 1 M HCl solution. (October 2022) - Oubaaqa, M.; Ouakki, M.; Rbaa, M.; Benhiba, F.; Galai, M.; Idouhli, R.; Maatallah, M.; Jarid, A.; Warad, I.; Lakhrissi, B.; Zarrouk, A.; Ebn Touhami, M.
Abstract: The inhibiting effect of two newly synthesized organic compounds based on 8-hydroxyquinoline, 2-amino-4-phenyl-2H-pyrano[3, 2-h]quinolin-3-carbonitrile (QP-H) and 2-amino-4-(4-methoxyphenyl)-2H-pyrano[3, 2-h]quinolin-3-carbonitrile (QP-OCH3 ), on mild steel (MS) corrosion in 1 M HCl has been assessed using various electrochemical techniques [potentiodynamic polarization curves (PP curves) and electrochemical impedance spectroscopy (EIS)], scanning electron microscopy (SEM), UV–visible spectroscopy, and theoretical calculations. The experimental results have revealed that QP-H and QP-OCH3 significantly prevent MS corrosion and that their inhibition efficacy improves upon increasing their concentration. The maximum inhibition efficiency of QP-H and QP-OCH3 was determined to be 92 and 79.1% at 10 −3  M, respectively. QP-H and QP-OCH3 are mixed-type inhibitors, according to our PP study. Thermodynamic specific data such as the energy, entropy and enthalpy of activation have been determined and discussed. The adsorption of BQMT and QMHC on the MS surface has been examined using SEM, UV–visible spectroscopy, and different isotherm models, which obeys the Langmuir isotherm model. Simulations based on density functional theory (DFT) and molecular dynamics simulation (MDS) have been used to further understand the corrosion resistance mechanism. Highlights: Biodiesel was synthesized from sunflower oil by the trans -esterification reaction. Aluminum is more resistant than stainless steel and copper with time of the biodiesel production. EIS data showed that the tested metals have a high corrosion resistance, through the formation of a passive layer. Data obtained by DFT and MD simulation support the results discovered by the experiment.